Regional Anesthesia in the Patient Receiving Antithrombotic or Thrombolytic Therapy: American Society of Regional Anesthesia and Pain Medicine Evidence-based Guidelines (Fourth Edition). Issue 1 (March 2019) - Horlocker, T.T.; Vandermeuelen, E.; Kopp, S.L.; Gogarten, W.; Leffert, L.R.; Benzon, H.T.
Abstract : ( Reg Anesth Pain Med . 2018;43:263–309) The American Society of Regional Anesthesia and Pain Medicine (ASRA) convened its Fourth Consensus Conference on Regional Anesthesia and Anticoagulation in conjunction with the European Society of Anesthesiology (ESA) in response to emerging patient safety issues. Among these are the heightened risk of neuraxial bleeding due to increasingly potent antithrombotic medications, changing standards for venous thromboembolism (VTE) prevention, and conflicting recommendations by various bodies and societies. Spinal hematoma is an uncommon and catastrophic complication of epidural or spinal anesthesia. Previous versions of this report have been published in 1998, 2003 and 2010 as ASRA Consensus Documents. For this update, authors performed a systematic and general review of relevant literature published between 2010 and 2017. The members represented ASRA, ESA, and the Society for Obstetric Anesthesia and Perinatology (SOAP).